2024
DOI: 10.1080/17482631.2024.2321645
|View full text |Cite
|
Sign up to set email alerts
|

“What about me?”: lived experiences of siblings living with a brother or sister with a life-threatening or life-limiting condition

Trine Brun Kittelsen,
Charlotte Castor,
Anja Lee
et al.

Abstract: Background There is a lack of knowledge regarding siblings’ experiences of being a brother or sister of a child with a life-threatening or life-limiting condition. Siblings’ perspectives are often expressed through their parents and not by siblings themselves. Method This study has a qualitative design within hermeneutic phenomenology. Thirteen siblings (ages 3–29) of children with cancer or genetic conditions participated in semi-structured interviews. Analyses followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In several studies, parents have identified the focus on siblings as an important but unmet parental need [ 3 , 25 , 50 ]. Parents feel stressed and overwhelmed by the care and attention needed by all of their children [ 5 ], as they feel forced to give priority to the needs of the ill child, meaning that siblings often come in second place [ 3 , 32 , 51 ]. Based on our findings, we suggest that practical assistance or respite care for the ill child can enhance parents’ QoL, as it creates the necessary space for parents to engage more fully with siblings.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, parents have identified the focus on siblings as an important but unmet parental need [ 3 , 25 , 50 ]. Parents feel stressed and overwhelmed by the care and attention needed by all of their children [ 5 ], as they feel forced to give priority to the needs of the ill child, meaning that siblings often come in second place [ 3 , 32 , 51 ]. Based on our findings, we suggest that practical assistance or respite care for the ill child can enhance parents’ QoL, as it creates the necessary space for parents to engage more fully with siblings.…”
Section: Discussionmentioning
confidence: 99%